Instrumentalidade do serviço social na previdência social no Brasil contemporâneo - Fernandes, Valmara Pordeus de Oliveira (2010)
In the sociability of the capital, the challenges to the consolidation of social security as a public policy become expressive, which has implications for social security services, particularly for Social Works who works for the security and fulfillment of social rights. Therefore, in this context of denial of these rights becomes relevant the work of social worker, as a professional committed to the ethical-political project and the Matrix Theory and Methodology of Social work, which potentiate the action able to establish professional articulated strategies for the strengthening of collective struggles for equality in society. Thus, this study examines the instrumentality of social work in the contemporary world and its contribution to the realization of rights. For this, we conducted a literature review, using authors dealing with the issue, as Behring (2008), Boschetti (2003), Mota (1995), Guerra (2007) among others, as well as documentary research through laws, decrees, instructions Normative, Internal Guidelines, and especially the analysis of the Matrix itself of Social Work in welfare. We use also of paramount importance to our analysis - the field research, using techniques such as semi-structured interview and questionnaire. The research enables the identification of important aspects of the subject studied, as the understanding of professionals about the instrumentality of Social Works in its ethical-political aspects, both theoretical and methodological and technicaloperative. The demands made by the managers for the profession on the sociooccupational have extrapolated the powers and duties of the Law Regulating the Profession and the Matrix of Social Work in welfare. The subjects of this study emphasize the role of social category of the National Institute of Social Security and the Federal Council of Social Service in defense of Social Works. The knowledge of social and institutional framework is critical to building control strategies that strengthen social security and public policy, the guarantor of social rights for workers in Brazil